Passing the Torch: An Introduction from New Editors-in-Chief Leisa Gibbons and Karen F. Gracy - Gibbons, Leisa; Gracy, K. (Walter de Gruyter, 2018)
© 2018 Walter de Gruyter GmbH, Berlin/Boston. As the new editors of Preservation, Digital Technology and Culture, we welcome you to our first issue of 2018! We would like to thank our previous editor-in-chief Michèle Cloonan heartily for her contributions to the journal, and also give thanks for her mentorship during the editorial transition. In her final column as editor, Michèle wrote that she had witnessed much change in the preservation discourse over the previous five years. Discussion of technological and social issues across a range of topics and disciplines were given space in PDT&C. The journal's coverage promoted a vision for a holistic and converged future of preservation that embodies multiple and varied ways of thinking and practice.